Strong uniqueness of solutions of stochastic differential equations with jumps and non-Lipschitz random coefficients - G. Kulinich; S. Kushnirenko (Modern Stochastics: Theory and Applications, 2014)
In the paper we establish strong uniqueness of solution of a system of stochastic differential equations with random non-Lipschitz coefficients that involve both the square integrable continuous vector martingales and centered and non-centered Poisson measures.